RELIGIOUS MODERATION AS A MECHANISM OF SOCIAL STABILITY IN A MULTICULTURAL CONTEXT: STUDY OF THE SASAK COMMUNITY - Hamdani Khairul Fikri; Andri Warseto (Universitas Islam Negeri Mataram, 2024)
Religious moderation is an important element in maintaining social harmony amidst the plurality of Indonesian society. This article aims to analyze the application of religious moderation in the Sasak community, Lombok, using Pierre Bourdieu's habitus theory as an analytical framework. This study uses a qualitative method based on literature review to explore the interaction between local traditions and religious values ??in shaping the practice of religious moderation. The results of the study indicate that the Sasak community has succeeded in internalizing the values ??of religious moderation through habitus formed from collective social experiences. Values ??such as tolerance, inclusiveness, and mutual cooperation are the main mechanisms in creating social stability amidst the challenges of globalization. In addition, the role of religious leaders, local traditions, and moderation-based education are key factors supporting the success of religious moderation. However, this study also notes obstacles in the form of the influence of globalization, radicalism, and economic inequality that can disrupt social harmony. Thus, religious moderation is not only relevant as a strategy to face global challenges, but also as a foundation for multicultural societies in maintaining social cohesion.